559 One Mesenteric Defect, Two Segments of Colon, A Number of Surgical Strategies! A Rare Case of An Internal Hernia Causing Bowel Ischemia. (12th October 2021) - Devani, P; Al-Saadi, N; Bowrey, D
Abstract: Internal hernias due to mesenteric defects are a rare cause of bowel obstruction, but once present their complications are associated with a high morbidity and mortality. We present the case of a 24-year-old patient who presented to the emergency department with signs and symptoms of an acute abdomen. Following surgical review, taking into consideration the patient's clinical, biochemical, and radiological findings, the patient was taken for immediate emergency surgical exploration. A laparoscopic approach was initially taken, which revealed dilated and ischemic colon, and therefore an open approach was then adopted. Operative findings included a very mobile caecum and proximal ascending colon which had herniated through a defect in the small bowel mesentery, the sigmoid colon had subsequently become incarcerated by the caecum and small bowel too. Both the ascending and sigmoid colon had become ischemic. A number of surgical strategies were considered, and given the patients age it was decided to preserve as much normal bowel as possible. Thus, a right hemi- and sigmoid colectomy were performed with an ileo-transverse anastomosis and formation of an end colostomy. In this case, radiological diagnosis pointed to a suspicion of an internal hernia, and operative diagnosis highlighted a rare mesenteric defect causing herniation and subsequent ischemia. Relying on the patient's clinical condition and an early decision for surgical intervention resulted in a positive outcome for outpatient. The patient made a good recovery following the bowel preserving surgery.